Passing the General Surgery Oral Board Exam - Neff, Marc A.; SpringerLink (Online service) (New York, NY : Springer New York : Imprint: Springer, 2014)
Edited by Dr. Marc Neff, Passing the General Surgery Oral Board Exam, Second Edition helps candidates prepare for the General Surgery Oral Board Exam in a different way than other review books. In addition to covering concepts frequently addressed on the test, the review also alerts you to "common curveballs" and "strikeouts"– the unexpected problems or seemingly benign actions (or inactions) that could result in a missed diagnosis or misdiagnosis, and thus result in failure to pass the exam. Fully updated and expanded to reflect the many changes in standards of care, this unique study guide is the first to expose the potential traps and pitfalls of the exam by providing examples of how the questions may be asked and what not to say in response.   Designed to be used in conjunction with medical textbooks and other study guides, Passing the General Surgery Oral Board Exam, Second Edition prepares candidates to think on their feet and answer exam questions confidently and accurately. It is an essential guide for surgical residents, fellows across the surgical subspecialties, and practicing surgeons who are board eligible.
Organizational Theme -- Breast -- Colon and Small Bowel -- Abdominal Endocrine -- Head and Neck Endocrine -- Esophagus -- Genitourinary -- Hepatobiliary -- Pancreas -- Pediatric -- Perioperative Care -- Skin and Soft Tissue -- Stomach and Duodenum -- Thoracic -- Trauma and Critical Care -- Vascular -- Conclusions: Last Curveballs Considerations.
Keywords: Surgery; Surgery; General Surgery